Viability validation of therapeutic cells according to surrounded amount of microbubbles and ultrasound exposure condition. (18th June 2019) - Seki, Masakazu; Otsuka, Takuya; Oitate, Riki; Masuda, Kohji; Unga, Johan; Suzuki, Ryo; Maruyama, Kazuo
Abstract: We previously reported methods of the active control of the cells by forming bubble-surrounded cells (BSCs), in which bubbles were attached to the surface of the cells, to enhance the controllability of the cells under ultrasound exposure. However, mechanical or biological damage to the cells contained in BSCs according to the conditions of ultrasound exposure has not been clarified. Therefore, we carried out the viability validation of the cells in BSCs versus various conditions of ultrasound exposure. First, we verified the reliability of cell viability by introducing two methods of CCK-8 assay and lactate dehydrogenase assay. Then, we confirmed that the surrounded amount of bubbles decreases the cell viability under continuous wave exposure rather than burst wave. We optimized the parameters to produce BSCs with the concentration of bubbles of 0.3 mg ml −1 and the concentration of the cells of 1.0 × 10 5 ml −1, to maintain the cell viability under ultrasound exposure. Also, using the maximum sound pressure lower than 300 kPa-pp, and low duty ratio less than 50%, the cell viability would be maintained more than 75% within the emission duration of 60 s.